The criminalization of gender abuse: a comparative analysis between Peruvian and Spanish penal regulations (2016)
Gender violence is one of the most serious manifestations of discrimination against women at the national and international level, so criminal law, as fragmentary mechanism for protect a legally interest, must play an important role in preventing this phe